Fundamental Approaches to Improving the Methodology of Developing Independent Creative Activity - Turaboeva Zilola Mukumtoshovna (Scientific Trends, 2025)
It is important to rely on fundamental pedagogical and psychological approaches to create effective methods that develop students' creative independence. These approaches not only help to transfer knowledge, but also involve the student as an active participant, encouraging him to think, choose, create and take responsibility for his actions. The article provides a theoretical analysis of the main approaches to improving the methodology of independent creative activity of students.
Keywords: Activity, pedagogical process, quality, independence, creative activity, self-development, self-education, independent creative activity, education, professionalism.